Physico-biochemical characteristics of fetal fluids in uterine torsion affected buffaloes - DEOSI, H S; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
Physical and biochemical characteristics of both allantoic and amniotic fluids of 19 uterine torsion affected buffaloes were compared with those of 13 dystocia other than uterine torsion and 8 normally calving buffaloes. In the torsion affected buffaloes, colour of allantoic fluid varied from reddish to dark brown (28.5% to 35 .6%, respectively) while the colour of amniotic fluid was dirty white in 45.4 % cases. The allantoic fluid of uterine torsion affected buffaloes had significantly higher (P<0.05) levels of urea, sodium, glutamate pyruvate transaminase (GPT), glutamate oxaloacetate transaminase (GOT) than normally calving buffaloes, while the amniotic fluid had significantly (P<0.05) higher levels of urea, phosphorus and GOT than both normally calving buffaloes and those suffering from dystocias other than uterine torsion. To conclude, the changes registered in certain biochemical parameters of fetal fluids in both torsion and dystocia affected buffaloes were merely the reflection of stress rather than an indicator of association with etiopathology of uterine torsion.